2013
DOI: 10.4025/actasciagron.v35i4.16552
|View full text |Cite
|
Sign up to set email alerts
|

<b>Culture systems in the production and quality of strawberry cultivars</b> - doi: 10.4025/actasciagron.v35i4.16552

Abstract: ABSTRACT. Until recently, strawberry cultivation was exclusively performed in soil using conventional cultivation methods, which resulted in many environmental and phytosanitary problems. Currently, soilless culture is the production method advocated for environmental reasons because it greatly reduces the use of chemical pesticide and fungicide inputs. This study assessed the yield and quality of fruits from strawberry cultivars grown in two systems (soil and substrate) in a greenhouse. The experiment was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
4
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 22 publications
6
22
4
9
Order By: Relevance
“…In our study, the greatest differences are found among strawberry cultivars. The total soluble solids, an important feature for the acceptance of the product by consumers, presented variation between the cultivars, as previously noted in several studies (Cecatto et al, 2013).…”
Section: Resultssupporting
confidence: 50%
“…In our study, the greatest differences are found among strawberry cultivars. The total soluble solids, an important feature for the acceptance of the product by consumers, presented variation between the cultivars, as previously noted in several studies (Cecatto et al, 2013).…”
Section: Resultssupporting
confidence: 50%
“…Os valores de sólidos solúveis observados neste trabalho estão dentro dos teores considerados para o morango que pode variar de 5,4 a 9,8° Brix, sobretudo devido às diferenças genéticas de cada cultivar [23,24] e também das condições de cultivo, colheita e armazenamento.…”
Section: Figura 2 Perda De Massa (%) De Frutos De Morangueiro Das Cuunclassified
“…Quando cultivado em solo, essa espécie é bastante suscetível ao ataque de fungos, bactérias e nematoides. Por isso, um dos principais problemas relacionados ao seu cultivo convencional é o uso excessivo de agrotóxicos (Cecatto et al 2013), cuja aplicação indiscriminada eleva o percentual de amostras com resíduos químicos em concentrações acima do limite estabelecido pela Agência Nacional de Vigilância Sanitária (ANVISA 2013). A rotação de áreas de plantio é fundamental para o manejo fitossanitário, mas não condiz com as principais unidades produtoras, em sua maioria, com pequenas áreas para o cultivo (Fernandes Júnior et al 2002).…”
Section: Introductionunclassified
“…As limitações fitossanitárias do solo também motivaram o desenvolvimento e o uso de técnicas de cultivo sem solo (Cecatto et al 2013). Cultivar morango em substrato, dentro de casas de vegetação, permite estender o período de cultivo (Ho 2004;Jafarnia et al 2010), extinguir o uso de produtos para desinfecção -como brometo de metila, cuja aplicação foi proibida no Brasil (Brasil 2002), reduzir o uso de agrotóxicos e, com isso, o consumo de alimentos contaminados e os danos ao ambiente ).…”
Section: Introductionunclassified